Genetic markers linked to Striga gesnerioides resistance for the improvement of Ghanaian cowpea (Vigna unguiculata) cultivars. (14th May 2019) - Essem, Frank; Ohlson, Erik W.; Asare, Aaron T.; Timko, Michael P.
Abstract: The parasitic plant, Striga gesnerioides (Willd.) Vatke, is one of the most important constraints of cowpea production and food security in West Africa. Currently, few Striga resistant cowpea varieties have been developed that are well‐adapted to the dry savannah regions of Ghana. While genes conferring resistance to Striga races SG1, SG3 and SG5 have been mapped, the genetic locus of resistance to the race of Striga found in Ghana (SG‐GH) has not been characterized. Here, we report identification of genetic markers linked to SG‐GH resistance and define the relationship of this locus to SG3 resistance in recombinant inbred line populations generated from crosses between Striga resistant IT97K‐499‐35 and the Striga susceptible varieties Apagbaala and SARC‐LO2. The populations were genotyped with five genetic markers associated with SG3 and SG5 Striga resistance genes and a genetic map was developed. Genes conferring resistance to SG‐GH and SG3 mapped 4.2 cM from each other on chromosome Vu11. The identification of genetic markers linked to SG‐GH resistance will facilitate the marker‐assisted development of high‐quality Striga resistant cowpea varieties in Ghana.